(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
It has been shown that photocyclization N-benzylamide acetoacetic acid in present three-ethanolamine or anhydryde acetic acid gives 2-oxo-4-methyl-5-phenyl-Δ3-pyrrolin. The formal kinetics of the process is given.